Fatigue life prediction for spot welds in coach-peel and lap-shear specimens with consideration of kinked crack behaviour. (24th February 2004) - Lin, S.-H.; Pan, J.
A fracture mechanics approach is adopted to examine the fatigue lives of spot welds in coach-peel and lap-shear specimens with consideration of kinked crack behaviour. The paths of fatigue cracks near the spot welds in these two types of specimens are first discussed. A fatigue crack growth model is then developed for spot welds in these two types of specimens based on the local stress intensity factor solutions for kinked cracks and the Paris law for crack propagation. Various global stress intensity factor solutions for spot welds in these two types of specimens are used to obtain the local stress intensity factor solutions with the experimentally determined kink angles. The results indicate that the fatigue life predictions based on accurate global stress intensity factor solutions can characterise the general trend of the experimental results. The effects of the kink angle on the fatigue life predictions are also discussed.